Gambaran Perilaku Pelajar SMA Negeri I Kakas Kabupaten Minahasa terhadap Bahaya Merokok - Pandelaki, August J.; Lampus, Benny S.; Sumilat, Yessica (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Smoking behavior is something a person does in the form of burns and smoke tobacco and causes smoke inhaled by people around him. As a result of exposure to secondhand smoke is not only active smokers but also the passive smokers. This is a descriptive study. The research sample is a few students SMA Negeri I Kakas were randomly selected and are willing to respondents. This study used a questionnaire distributed to selected respondents. Conclusion: Picture of student knowledge and attitude towards the dangers of smoking were categorized either. While the action on the dangers of smoking is not considered good. Keywords: Student, The Behavior of The Dangers of Smoking